Romania : Romania-Seventh and Eighth Reviews Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses Romania's Seventh and Eighth Reviews Under the Stand-by Arrangement and Request for Waiver of Nonobservance of Performance Criteria. Continued strong fiscal consolidation would enable Romania to exit the EU Excessive Deficit Procedure by mid-2013; prudent monetary policy kept core inflation low, and close supervision buttressed banking sector stability. Fiscal and international reserves buffers and a well-capitalized banking sector provide a cushion against shocks. Market sentiment toward Romania improved as political uncertainty subsided in the aftermath of the December 2012 parliamentary elections, which the ruling coalition won. Structural reforms, however, advanced slowly, and the recovery has lagged behind that in most other European emerging economies.